Permainan Bolang (Studi Pengembangan Cabang Olahraga Baru Untuk Kompetisi Anak Berpendidikan Inklusi) - Kumbara, Hengki; Imansyah, Farizal; Sari, Puput Sekar (JSKK (Jurnal Sains Keolahragaan dan Kesehatan), 2024)
The purpose of this study was to determine the development of a valid and effective bolang game model for inclusive education children. The research method is a research and development method by adopting the Borg and Gall stages into three stages, namely research, development and diffusion. The expert validators of the research include expert game validators and competition experts in the field of inclusive education. Data collection using a questionnaire sheet (questionnaire). Data analysis using percentage analysis. This study concluded that the bolang game model for inclusive education children's competitions was declared very valid with an average expert validation of 93.5%. The results of the field trial explained that the small scale had a percentage of 91.6 while the large scale was 89.5 with very good criteria. The bolang game is a term for a hole ball game, played using both hands to put the ball into a small hole as a target. The bolang game model can be used as a media for competitive sports of choice for inclusive education children, due to limited access to space for movement, making it difficult to do the types of sports that are usually played by normal children.